Asthma management in a specialist setting: Results of an Italian Respiratory Society survey. (June 2017) - Braido, Fulvio; Baiardini, Ilaria; Alleri, Pietro; Bacci, Elena; Barbetta, Carlo; Bellocchia, Michela; Benfante, Alida; Blasi, Francesco; Bucca, Caterina; Busceti, Maria Teresa; Centanni, Stefano; Colanardi, Maria Cristina; et al.
Abstract: Background: Asthma considerably impairs patients' quality of life and increases healthcare costs. Severity, morbidity, and degree of disease control are the major drivers of its clinical and economic impact. National scientific societies are required to monitor the application of international guidelines and to adopt strategies to improve disease control and better allocate resources. Aim: to provide a detailed picture of the characteristics of asthma patients and modalities of asthma management by specialists in Italy and to develop recommendations for the daily management of asthma in a specialist setting. Method: A quantitative research program was implemented. Data were collected using an ad hoc questionnaire developed by a group of specialists selected by the Italian Pneumology Society/Italian Respiratory Society. Results: The records of 557 patients were analyzed. In the next few years, specialists are expected to focus their activity patients with more severe disease and will be responsible for selection of patients for personalized biological therapy; however, only 20% of patients attending Italian specialist surgery can be considered severe. In 84.4% of cases, the visit was a follow-up visit requested in 82.2% of cases by the specialist him/herself. The Asthma Control Test is used only in 65% of patients. When available, a significant association has been observed between the test score and asthma control as judged by the physician, although concordance was only moderate (κ = 0.68). Asthma was considered uncontrolled by the specialist managing the case in 29.1% of patients; nevertheless, treatment was not stepped up in uncontrolled or partly controlled patients (modified in only 37.2% of patients). Conclusions: The results of this survey support re-evaluation of asthma management by Italian specialists. More resources should be made available for the initial visit and for more severely ill patients. In addition, more extensive use should be made of validated tools, and available drugs should be used more appropriately.